Era Digital dan Eskalasi Radikalisme - Jesroy, Jesroy; Sirait, Hikman; Lie Lie, Tju (Peneliti.net, 2025)
The digital era has significantly changed the existence of social and religious communities, including in the spread of dogmatic teachings that build the faith and identity of religious communities. However, digital transformation has also opened up space for the growth of religious radicalism, which is spread massively and uncontrollably through social media and digital platforms. The Church, as a religious institution, faces serious challenges in nurturing its congregation amid ideological currents that threaten the values of tolerance and diversity. The phenomenon of religious identity fragmentation, characterised by exclusivism, polarisation, and narratives of religious superiority or claims to truth, further exacerbates the potential for intra- and inter-religious conflict. The purpose of this study is to examine the role of the church in shaping a tolerant theological mindset as a response to radicalism in the digital age. The method used is a descriptive qualitative approach through literature study. It can be concluded that Christianity can understand the nature of the digital age and the narrative of religious radicalism, as the digital age has become a new space for the rapid spread of religious radicalism narratives through social media and online platforms. This situation exacerbates the fragmentation of religious identity, where believers become increasingly polarised. Therefore, the church has a responsibility to shape a tolerant theological reasoning that can embrace differences and restore the integrity of faith identity amid the challenges of the digital age.